Remaja yang mengalami stunting cenderung memiliki kebugaran fisik yang rendah - Andra Kurnianto; Benny Sana Putra (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
This research to assess physical fitness in stunted and normal-stature adolescents aged 13-15 years old. This cross-sectional, comparative study was carried out at a junior high school in Mukomuko, Bengkulu, Indonesia. Physical fitness was measured using a physical fitness test for Indonesian Adolescents, i.e., sprint, pull-up, sit-up, jump-up, and run. Physical activity level was assessed using the Physical Activity Questionnaire for Adolescents (PAQ-A). Stature-for-age was evaluated by using the WHO growth charts (Software WHO AnthroPlus version 1.0.4). There were 200 adolescents, consisting of 101 (50.5%) males and 99 (49.5%) females. The average physical fitness score of normal stature (14.3+2.3) was higher than that of stunted Adolescents (12.6+2.4). Stunted adolescents had significantly lower physical fitness than normal-stature adolescents (OR 3.25, 95% CI 1.617-6.550, P < 0.05). Regression analysis showed that stature significantly impacted physical fitness (p<0.05). Apparently, 9.4% of the variance in physical fitness can be explained by stature variables. The findings of this study underscore the urgent need for further research in this area.